The Analysis of Muzara'ah System Implementation With the Prosperity of Non-Land Owning Rubber Tree Farmers in Bintais Julu village - Ila Nasution; Fadhila Rahma, Tri Inda; Harianto, Budi (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
Farmers' welfare is when they have a good quality of life and adequate economic stability. Welfare is not only in the economy but also in social matters such as health, education and the environment. This study aims to determine the analysis of the application of the muzara'ah system to the welfare of farmers in Bintais Julu. The method used is a quantitative approach through distributing questionnaires to respondents with the census method to 35 respondents including landowners and tenant farmers in North Padang Lawas Regency. The results of this study indicate that the muzara'ah system provides a positive and significant relationship to the welfare of farmers. It can be concluded that the muzara'ah system has a significant effect on the welfare of farmers. This muzara'ah system has a relationship of 13.6% while the remaining 86.4% is influenced by other variables not examined in this study. The muzara'ah system provides employment opportunities for sharecroppers and helps landowners in managing their gardens so as to create increased welfare between the two parties so that this system needs to be applied more widely.